STRATEGI KOMUNIKASI DAKWAH KULTURAL WALI SONGO MELALUI PERTUNJUKAN WAYANG KULIT - Muh. Mirwan Hariri; A. Fikri Amiruddin Ihsan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study examines the cultural da'wah communication strategies of the Wali Songo, particularly through the medium of shadow puppet performances in the 15th to 16th centuries in Java. The main focus of the study is to understand how Sunan Kalijaga and other saints were able to use local arts as a means of spreading Islamic values ​​peacefully and accepted by Javanese society without major conflicts. This study uses qualitative methods with a literature study approach, historical analysis, and cultural interpretation. The results show that the cultural da'wah strategies carried out include the selection of popular media (shadow puppets), modification of the form and narrative of the story to suit the principles of monotheism, and the creation of Punakawan figures as symbols of da'wah close to the lives of the people. The analysis also shows that the core da'wah messages include monotheism, social morality, and jihad against lust. In the discussion, this study compares the cultural da'wah strategies of the Wali Songo with contemporary da'wah strategies in the digital era. The results found that the principles of media adaptation, symbolism, and persuasive approaches remain relevant today. This research contributes to the development of cultural da'wah communication theory and provides inspiration for digital da'wah strategies in the 21st century.